Evaluation of von Willebrand factor phenotypes and genotypes in Hemophilia A patients with and without identified F8 mutations. (9th May 2015) - Boylan, B.; Rice, A. S.; De Staercke, C.; Eyster, M. E.; Yaish, H. M.; Knoll, C. M.; Bean, C. J.; Miller, C. H.; the Hemophilia Inhibitor Research Study Investigators; Abshire, T. C.; Dunn, A.; Kempton, C. L.; et al.
Summary Background Hemophilia A (HA) is an X‐linked bleeding disorder caused by a deficiency in factor VIII (FVIII). von Willebrand disease (VWD) is characterized by a quantitative or qualitative defect in von Willebrand factor (VWF). Patients with VWD with severely low VWF or VWD Type 2N (VWD2N), a VWD subtype distinguished by defective VWF binding to FVIII, may have reduced FVIII levels secondary to their VWD. These patients superficially resemble patients with HA and pose a potential for misdiagnosis. Objectives To investigate the unexplained cause of bleeding in HA patients without known FVIII mutations by assessing plasma VWF antigen (VWF:Ag), FVIII binding capacities and VWF genotypes. Patients/Methods Thirty‐seven of 1027 patients with HA studied as part of the Hemophilia Inhibitor Research Study lacked identifiable F8 mutations. These patients (cases) and 73 patients with identified F8 mutations (controls) were evaluated for VWF:Ag, a patient's VWF capacity to bind FVIII (VWF:FVIIIB) and VWF sequence. Results Four cases had VWF:Ag < 3 IU dL−1 and VWF mutations consistent with Type 3 VWD. Six cases and one control were heterozygous for mutations previously reported to cause Type 1 VWD (VWD1) (n = five cases and one control) or predicted to be deleterious by Polyphen2 and SIFT prediction tools (n = 1 case). One control had VWF:Ag < 30 IU dL−1 and seven patients (four cases and three controls), including two cases who were heterozygous for a known VWD2N mutation, had reduced VWF:FVIIIB. Conclusions These data emphasize that some patients diagnosed with HA require VWF assessments in order to achieve a comprehensive diagnosis and an optimal treatment strategy.